Evaluating Inclusion as a Multidimensional Science, Technology and Innovation Policy Objective - Kalliomäki, Helka; Kuusisto, Jari; Kunttu, Leena (De Gruyter, 2024)
Inclusion, as an increasingly important science, technology and innovation (STI) policy objective, is seen as a key to global sustainable innovation. Yet the concept’s usage in both practitioner, policy and research language is often fuzzy. Inclusion is used in wide variety of contexts, not just those that have been traditionally associated with the concept such as marginalized groups and communities. The objective of this chapter is to unpack different dimensions of inclusion as an STI policy objective and as an object of evaluation in an increasingly complex innovation space. The chapter presents a schematic conceptual framework of the different approaches that can be used to steer evaluation practice. It also maps future research directions for evaluating inclusion.
Keywords: fi=Aluetiede|en=Regional Studies|